2016
DOI: 10.1177/1077546316667178
|View full text |Cite|
|
Sign up to set email alerts
|

Nonlinear dynamic response analysis on gear-rotor-bearing transmission system

Abstract: A coupled lateral-torsional nonlinear dynamic model with 16-degree-of-freedom (16-DOF) of gear-rotor-bearing transmission system (GRBTS) is developed after comprehensive considering the nonlinear features associated with time-varying meshing stiffness, backlash, transmission error, friction force, input/output load, gravity and gear eccentricity. Based on the nonlinear differential equations, the coupled multi-body dynamic responses of the GRBTS are demonstrated using the Runge-Kutta numerical method, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 32 publications
3
26
0
Order By: Relevance
“…In any wind turbine drive train, the effect that causes the greatest non-linearity is related to the friction force. The results of Zhou et al [37] show that the friction force could increase the amplitude of the vibration and seriously affect the low frequency components. It is not easy to carry out the friction compensation, in fact, it still is an open research topic [38].…”
Section: Experimetal Resultsmentioning
confidence: 99%
“…In any wind turbine drive train, the effect that causes the greatest non-linearity is related to the friction force. The results of Zhou et al [37] show that the friction force could increase the amplitude of the vibration and seriously affect the low frequency components. It is not easy to carry out the friction compensation, in fact, it still is an open research topic [38].…”
Section: Experimetal Resultsmentioning
confidence: 99%
“…where static transmission error e(t) is caused by manufacture and assembly, and r b1 and r b2 are gear base circle radii. is error can be treated as a sinusoidal function e(t) � e 0 + e r sin(ω m t + φ m ) [9], where e 0 and e r severally represent mean and amplitude of the error, and φ m and ω m are, respectively, initial phase and meshing frequency. ω m meshing frequency is expressed as ω m � 2πn 1 z 1 /60(2πn 2 z 2 /60).…”
Section: Lumped Mass Model Of the Gearmentioning
confidence: 99%
“…Many outstanding scholars have made great contributions to the research of healthy gear system. Zhou et al [9] presented a coupled lateral-torsional 16-DOF gearrotor-bearing system considering piecewise periodic stiffness, friction, and eccentricity, and the motion states and frequency variations were analyzed in detail. In addition, the backlash is an important factor to ensure smooth and reliable operation.…”
Section: Introductionmentioning
confidence: 99%
“…Walha et al [9] investigated dynamics of a two-stage gear system involving backlash and timedependent mesh stiffness, and the decomposition of a nonlinear system into some linear systems was solved by the Newmark iterative algorithm. Zhou et al [10] developed a coupled lateral-torsional nonlinear dynamic model with 16 degrees of freedom (16-DOF) of gear-rotor-bearing transmission system considering the nonlinear features, and the mean load excitation had a complicated influence on the coupled system; they concluded that the torsional vibration was the dominant response in the geared system. Chen et al [11] detected the key shafts of the four-stage helicopter gearbox and analyzed their sensitivity to each branch of the system through the lumped mass method.…”
Section: Introductionmentioning
confidence: 99%